Morphological Errors in Descriptive Students’ Writing - Haris, Hannisa (Journal of English Language and Education, 2023)
This study analyzed the morphological errors that occurred in students’ descriptive writing using surface strategy taxonomy in error analysis. Further, this qualitative research describes the common morphological errors that appeared in students’ descriptive writing. The data were derived from 70 students’ descriptive writing of grade XI consisting of 2 classes. They were taken by using a simple random sampling method. The data were classified by using surface strategy in error analysis and were analyzed by using qualitative data analysis The result of the research showed that some errors occurred at the morphological level. They include inflection, derivation, preposition, article, copula be, pronoun, and auxiliary verbs.  Inflection is a common error that mostly appeared with a percentage of 39%, while preposition is the lowest number of morphological errors with a percentage of 2 %. It also found that 73%  of omission errors frequently appeared in students' descriptive writing. Thus, it illustrated that many students still mostly omitted some inflection, derivation, preposition, article, copula be, pronoun, and auxiliary verbs.